Global Library and Information Science Research Patterns: A Twenty-Five-Year Reflection - Elia, Emmanuel Frank; Mhando, Joseph Andrew (University of Dar es Salaam Library Journal, 2024)
This paper reports the findings of a desk review research on global changes in Library and Information Science (LIS) research. Specifically, the review examined articles published in a 25-year (1995-2020) span of LIS research trends using Google database. The variables in the examination were gender, citation patterns, institutional affiliation, and degree of collaboration. To collect data from 43 articles, the study applied a bibliometric method, with the resultant data subjected to content analysis. The study found that male authors published more on the theme of LIS research trends than their female counterparts. Moreover, the results indicate a positive and significant correlation between the duration of a publication and the number of citations. The number of years of publication and open access publishing had a positive but non-statistically significant relationship with citation. Furthermore, the study found authorship collaboration to be moderate at 0.581. There was also a marked shift from traditional to new LIS research areas related to digital technology and its application in libraries. Overall, the trends in LIS research appear attributable to research infrastructure, sufficient funding, access to data, and the researcher ' s skills. These findings support enhancing capacity building for LIS researchers to update their skills as part of concerted efforts to enable them to meet global changing needs.